Current status of robot‐assisted laparoscopic pancreaticoduodenectomy and distal pancreatectomy: A comprehensive review. Issue 3 (28th May 2013) - Lai, Eric CH; Tang, Chung Ngai
Abstract Background This article reviews the current status of robot‐assisted laparoscopic pancreaticoduodenectomy and distal pancreatectomy. Method Searches of MEDLINE and PubMed databases were conducted using the keywords "laparoscopic pancreatectomy, " "robotic surgery, " "pancreaticoduodenectomy" and "distal pancreatectomy" to find articles published between January 1990 and September 2012. Additional papers were identified by a manual search of the references in key articles. Results Only cases reports, cohort series and nonrandomized comparative studies were available to validate the outcomes of robotic pancreaticoduodenectomy and distal pancreatectomy. There was no randomized controlled trial comparing the robotic approach to the laparoscopic or open approach. To the best of our knowledge, only four studies have compared the robotic approach and the open approach for pancreaticoduodenectomy, and four studies have been published comparing the robotic approach and the laparoscopic approach for distal pancreatectomy. The data were difficult to interpret because of the heterogeneity of the pathologies and techniques used. Robotic‐assisted laparoscopic pancreaticoduodenectomy and distal pancreatectomy for appropriately selected patients can be performed safely, with postoperative complication rates and mortality rate comparable to results observed with laparoscopic or open techniques. Robotic surgical systems also seem to improve the spleen‐preservation rate in distal pancreatectomy. The oncologic outcomes have not yet been adequately evaluated. Conclusions Robotic pancreaticoduodenectomy and distal pancreatectomy are safe and feasible in appropriately selected patients. However, because of uncertainties regarding long‐term oncologic outcome, caution should be exercised in assessing the appropriateness of this operation for individual patients. Further randomized and controlled studies are required to support the routine use of the robotic technology for pancreatectomy.